2012
DOI: 10.11005/jbm.2012.19.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cornus Officinalis on Receptor Activator of Nuclear Factor-kappaB Ligand (RANKL)-induced Osteoclast Differentiation

Abstract: ObjectivesOsteoporosis is a disease of bones that is thought to result from an imbalance between bone resorption and bone formation. Although osteoporosis itself has no symptoms, osteoporosis caused by osteoclasts leads to an increased risk of fracture. Here we examined the effects of cornus officinalis on receptor activator of nuclear factor-kappaB ligand (RANKL)-mediated osteoclast differentiation.MethodsWe evaluated the effects of cornus officinalis on RANKL-induced osteoclast differentiation from bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…Isolated cells were incubated with RANKL and M-CSF for osteoclast differentiation and co-treated with single or three different ratios of CO and AJ mixtures (9:1, 8:2, and 7:3) for 6 days. As a result, both CO and AJ (10 and 50 μg/mL) extract in our study did not affect cellular proliferation ( Supplementary Figure S3 ), but inhibited TRAP activity ( Supplementary Figure S4 ), as previously described in the literature [ 18 , 32 ]. In addition, mixtures of CO and AJ did not show toxic effect to osteoclasts during the differentiation period ( Figure 3 B).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Isolated cells were incubated with RANKL and M-CSF for osteoclast differentiation and co-treated with single or three different ratios of CO and AJ mixtures (9:1, 8:2, and 7:3) for 6 days. As a result, both CO and AJ (10 and 50 μg/mL) extract in our study did not affect cellular proliferation ( Supplementary Figure S3 ), but inhibited TRAP activity ( Supplementary Figure S4 ), as previously described in the literature [ 18 , 32 ]. In addition, mixtures of CO and AJ did not show toxic effect to osteoclasts during the differentiation period ( Figure 3 B).…”
Section: Resultssupporting
confidence: 87%
“…Cornus officinalis (CO) and Achyranthes japonica (AJ) have traditionally been used as herbal medicines in East Asia for their anti-oxidative, anti-inflammatory, and anti-cancer effects [ 15 , 16 , 17 ]. Previous studies have reported that CO inhibited osteoclast differentiation and promoted osteoblast differentiation, and AJ exhibited osteoprotective effects in ovariectomized (OVX) mice [ 18 , 19 , 20 , 21 ]. Although the individual anti-osteoporotic effects of Cornus officinalis (CO) and Achyranthes japonica (AJ) have been demonstrated, the synergistic effects of combined CO and AJ on osteoporosis have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, the protein expression of c-Fos and NFATc1 is also suppressed as well as the RANKL-induced degradation of IκB kinase (Kim J. Y. et al, 2012). Morroniside ( 8 ), one the main constituent of extracts from C. officinalis fruits, has been studied on osteoarthritis in human chondrocytes.…”
Section: Unique Biological and Pharmacological Activities Of C Mas Amentioning
confidence: 95%
“…Reduce protein and mRNA levels of c-Fos, NFATc1, OSCAR, and TRAP. Inhibit phosphorylation of p-38 and c-JNK and degradation of I-κB [ 57 ] Promoting melanogenesis activity Methanol extract Melan-a cell lines Increase the production and activity of tyrosinase. Increase MITF-M mRNA level and TRP-1&2 production [ 58 ] Immunomodulatory activity Aqueous extract C57BL/6 mice are transplanted with a skin graft from Balb/C donors Prolong skin allograft survival.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Firstly, sweroside (at 7.5 µg mL −1 ) for 1 week significantly promoted the proliferation and differentiation of osteoblasts via the regulation of osteocalcin [ 56 ]. Also, CF extract (at 0–100 µg mL −1 ) for 4 days significantly inhibited osteoclast differentiation in a dose-dependent manner via the inhibition of the signaling cascades NF-κB/c-Fos/NFATc1 to improve osteoporosis [ 57 ]. Secondly, CF methanol extract (at 3.125–12.5 µg mL −1 ) for 3 days significantly up-regulated synthesis and activity of tyrosinase, raised TRP-1&2 translation associating with increasing transcription of MITF-M, finally promoted melanogenesis by 36.1% [ 58 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%